QuEChERS sample pre-processing with UPLC–MS/MS: A method for detecting 19 quinolone-based veterinary drugs in goat’s milk - Bang Ye, Siou; Huang, Ying; Lin, Ding-Yan (Food chemistry, 2022)
•QuEChERS + UPLC–MS/MS was used to determine and identify quinolones in goat’s milk.•Plackett–Burman and CCD methods identified efficient extraction parameters.•The developed method meets the validation specifications of the TFDA.•The method is suitable for the routine analysis of quinolones in goat’s milk. We develop and validate a method for the rapid determination and identification of 19 quinolones in goat’s milk by combining the QuEChERS technique with ultra-performance liquid chromatography–tandem mass spectrometry. Plackett–Burman and Central Composite Design methods were used to select the parameters that best promote the extraction efficiency, which led to extraction with acetonitrile/5% formic acid, followed by phase separation with sodium citrate, disodium hydrogen citrate, Na2SO4, and NaCl as optimal. The supernatant was then extracted and cleaned by dispersive solid-phase extraction using C18 and Na2SO4 aided by low-temperature clean-up. The method was validated, with limits of quantification (LOQs) of 5 ppb, specificities of 1/5 LOQ, linearities (R2) > 0.9853, recoveries of 73.4–114.2%, repeatabilities < 15.0%, and intermediate precisions < 13.6%. The developed method was suitable for the routine analysis of quinolone residues in goat’s milk and was used to test 10 goat milk samples produced in Taiwan.